The Removal of Cationic Dyes Using Coconut Husk as an Adsorbent - Low, K. S.; Lee, C. K. (1990)
The ability of coconut husk to remove methylene blue from solution was investigated. Factors such as initial dye concentration, contact time, adsorbent dosage and pH of solution were studied. Results show that Langmuir isotherm can be successfully applied to the methylede blue - coconut husk system and that coconut husk is a suitable adsorbent for such a dye. Maximum adsorption capacity is 99 mg gl moss as derived from Langmuir isotherm. A series of fixed bed experiments was carried out and the results were applied to a bed-depth/service time model for column adsorption. The validity of such a model is discussed.